Pola Penegakan Hukum dalam Pengurangan Aktifitas Ilegal untuk Perlindungan Habitat Harimau Sumatera (Panthera tigris sumatrae) di Tambling Wildlife Nature Conservation, Taman Nasional Bukit Barisan Selatan - Ardi Bayu Firmansyah; Muhammad Ali Imron; Richo Andi Wibowo; Guntur Wibawa Mukti; Risgianto Risgianto; Maria Edna Herawati (Jurnal Ilmu Kehutanan, 2021)
Law enforcement plays a vital role to prevent the extinction of endangered species, including the Sumatran tiger. We investigated the roles of private sector involvement in Tambling Wildlife Nature Conservation (TWNC) for supporting law enforcement by Bukit Barisan Selatan National Park (BBSNP) agencies. We explored the relationship between law enforcement in the environment and forestry on illegal activities within the habitat of the Sumatran tiger in the TWNC area. We collected data on law enforcement and illegal activities during the period of 2000-2018 from BBSNP and TWNC management through secondary data and conducted semi-structured interviews with selected persons, including managers and staff. Additional data on illegal activities data was also obtained through the SMART programme. Our study showed that law and non-law enforcement approaches on environment and forestry during 2001-2018 reduced illegal activities within the TWNC area. However, the approach was not effective to reduce illegal activities if not implemented synergistically. This was evidenced by the guard posts burning case in the TNWC area. We highlighted that the law and non-law enforcement approach on environment and forestry must be implemented involving more synergy ways to reduce illegal activities in the habitat of Sumatran tiger in TWNC.